Investigation of potential toxicity associated with long-term amitriptyline exposure: Evidence from genomics - Jiachen Liu; Zihan Li; Zebin Deng; Yinhuai Wang; Fei Deng (Ecotoxicology and Environmental Safety, 2025)
The increasing environmental detection of antidepressants such as amitriptyline (AT) has raised toxicological concerns, yet its long-term safety profile remains poorly characterized. We applied an integrative strategy combining phenome-wide association studies (PheWAS), Mendelian randomization (MR), network toxicology, and molecular docking to systematically evaluate potential adverse effects of AT. PheWAS analyses were performed across 784 phenotypes using UK Biobank and FinnGen (R10). Among these, loss-of-function mutations in AT targets SLC6A2 and SLC6A4 showed significant associations after multiple-testing correction with pancreatic cancer and erythematous conditions, respectively. Complementary MR analyses using GTEx v8 tissue-specific cis-expression quantitative trait loci (eQTLs) and multiple autoimmune and inflammatory genome-wide association study (GWAS) datasets demonstrated that elevated expression of SLC6A2 and SLC6A4 conferred protective effects against systemic lupus erythematosus, psoriasis, rosacea, and erythema nodosum across tissues, supporting the causal relevance of these pathways. Network toxicology based on protein-protein interactions (STRING v11.5, Cytoscape v3.10.1) and functional enrichment (ClusterProfiler v4.10.0) highlighted immunoinflammatory, neuroendocrine, and ion channel regulatory mechanisms potentially involved in AT-induced toxicity. Finally, molecular docking simulations (AutoDock Vina v1.2.7, AlphaFold structures) provided structural evidence for AT interactions with key targets including TRPV1. Collectively, these findings suggest that pharmacological inhibition or environmental accumulation of AT may contribute to inflammatory skin reactions and pancreatic tumorigenesis through multiple converging molecular pathways.